2011
DOI: 10.4314/gmj.v45i1.68918
|View full text |Cite
|
Sign up to set email alerts
|

Potential sources of transmission of hospital acquired infections in the volta regional hospital in Ghana

Abstract: SUMMARYObjective: To determine the prevalence of female genital schistosomiasis in riparian communities in the Volta basin of Ghana, Design: The study was a cross-sectional study conducted among women 15-49 years in the Volta Basin. Urinary schistosomiasis prevalence was determined using microscopy.A structured questionnaire was also administered to collect information on the demography, obstetric history and reproductive health experiences. Cervical punch biopsy was collected from women who consented to be sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 25 publications
0
35
1
2
Order By: Relevance
“…In Ghana, however, a similar study by Tagoe et al (2011) isolated a high percentage of S. aureus and E. coli as well as Bacillus spp. on fomites at the Volta Regional Hospital which indicated a high potential risk of nosocomial infections in that hospital.…”
Section: Author(s) Agree That This Article Remains Permanently Open Amentioning
confidence: 82%
“…In Ghana, however, a similar study by Tagoe et al (2011) isolated a high percentage of S. aureus and E. coli as well as Bacillus spp. on fomites at the Volta Regional Hospital which indicated a high potential risk of nosocomial infections in that hospital.…”
Section: Author(s) Agree That This Article Remains Permanently Open Amentioning
confidence: 82%
“…In the current study 30 isolates out of 231 showed >90 % inhibition against S. epidermidis and were further screened for broad range antibacterial activity. Other indicator organisms used in the current study belong to gram positive (M. luteus) and gram negative (E. coli and P. fluorescence) clan and have been reported to cause nosocomial infection [16,[19][20][21]. These infections persist and are resilient to antibiotic treatment.…”
Section: Molecular Characterization Of Potential Candidatementioning
confidence: 99%
“…The broad spectrum of bacteria isolated here is indicative of the potential of the mobile phones to act as a fomite in similar fashion to paper currency, stethoscopes, ball point pen etc. [11][12][13][14]. This aspect of mobile phones is still unexplored and needs research.…”
Section: Fig 1-contamination Rates Across Different Wardsmentioning
confidence: 99%